Innate lymphoid cells: The missing part of a puzzle in food allergy. Issue 7 (16th March 2021) - Sahiner, Umit M.; Layhadi, Janice A.; Golebski, Korneliusz; István Komlósi, Zsolt; Peng, Yaqi; Sekerel, Bulent; Durham, Stephen R.; Brough, Helen; Morita, Hideaki; Akdis, Mübeccel; Turner, Paul; Nadeau, Kari; et al.
Abstract: Food allergy is an increasingly prevalent disease driven by uncontrolled type 2 immune response. Currently, knowledge about the underlying mechanisms that initiate and promote the immune response to dietary allergens is limited. Patients with food allergy are commonly sensitized through the skin in their early life, later on developing allergy symptoms within the gastrointestinal tract. Food allergy results from a dysregulated type 2 response to food allergens, characterized by enhanced levels of IgE, IL‐4, IL‐5, and IL‐13 with infiltration of mast cells, eosinophils, and basophils. Recent studies raised a possible role for the involvement of innate lymphoid cells (ILCs) in driving food allergy. Unlike lymphocytes, ILCs lack They represent a group of lymphocytes that lack specific antigen receptors. ILCs contribute to immune responses not only by releasing cytokines and other mediators but also by responding to cytokines produced by activated cells in their local microenvironment. Due to their localization at barrier surfaces of the airways, gut, and skin, ILCs form a link between the innate and adaptive immunity. This review summarizes recent evidence on how skin and gastrointestinal mucosal immune system contribute to both homeostasis and the development of food allergy, as well as the involvement of ILCs toward inflammatory processes and regulatory mechanisms.